Graphitic carbon nitride-derived high lithium storage capacity graphite material with regular layer structure and the structural evolution mechanism. (20th March 2022) - Yuan, Zhipeng; Hu, Zhuang; Gao, Peng; Zhang, Weihua; Tang, Yu; Li, Lingfang; Shi, Kui; Han, Shaochang; Fan, Changling; Liu, Jinshui; Liu, Jilei
Highlights: A novel graphite material is constructed by using g-C3 N4 as precursor. Nickel powder plays the denitrification role proved by the TG-MS analysis. The catalytic graphitization mechanism of nickel powder is investigated. The intermediate Ni3 C plays vital role in the graphitization of g-C3 N4 . The carbide conversion mechanism is dominated in the catalytic mechanism. Abstract: A novel graphite anode (Ni-g-C3 N4 ) is synthesized by using graphitic carbon nitride as the precursor and nickel (Ni) as the catalyst, which dramatically decreases the reaction temperature to 850 °C. The critical role of Ni in denitrifying g-C3 N4 to produce high-quality graphite is identified, with the results showing that the nitrogen content decreases from 62.1% to 1.2% and thus leading to greatly enhanced electrical conductivity as well as excellent rate capability, cycle performance and structure integrity. The Ni-g-C3 N4 exhibits typical low voltage plateau characteristic of graphite anode and the transformation of graphite intercalation compounds are investigated in the in-situ XRD analysis during the discharge/charge process. The capacity retention is as high as 99.3% after 600 cycles at 0.5 A⋅ g −1, demonstrating excellent structural stability. Moreover, the evolution from g-C3 N4 to graphite Ni-g-C3 N4 is investigated via TG-MS and high-temperature in-situ XRD, which clearly reveals that the catalytic graphitization processes mainly consist of the dissolution, re-precipitation and carbide conversion, along with the formation of intermediate Ni3 C and the release of nitrogen gas. In general, this work not only proposes a novel method to synthesize high performance graphite anode from g-C3 N4 for lithium ion batteries, but also unravels the catalytic graphitization mechanism. Graphical abstract: Image, graphical abstract